Effects of low temperature, starvation and oxidative stress on the physiology of Campylobacter jejuni cells - Klančnik, Anja (Array, 2008)
Summary: Campylobacter jejuni is a food-borne pathogen that causes diarrheal diseases in humans and animals. Still unknown mechanisms allow the cells to overcome significant stresses despite the absence of several traditional stress response genes. C. jejuni is problematic because of its ability to adapt and survive in various conditions of extraintestinal environment, common to food production and supply chain. The authors demonstrated that preliminary exposure to 25 °C did not influence the heat resistance of C. jejuni cells at 55 °C. In addition, changes of morphology, culturability and viability were noticeable for fed and starved cultures exposed to low temperature and oxidative stresses. All physiology changes were influenced by starvation and, to a lesser extent, by other stresses. Starvation was the most significant factor in C. jejuni survival, coccoid cell formation and especially culturability. Temperature downshift, oxidative stress and starvation, usually in combination with other factors, can trigger transition of bacteria to a viable but nonculturable state. Results showed substantial variability in responses to stresses applied, indicating no correlation between low temperature and oxidative stress response of campylobacters. Understanding of microbial physiology after exposure to various stresses is essential for food safety